Reduction of Sound Pressure Levels with Noise Barriers Containing Agricultural Residues: Case Study - Tinnam, Pasit; Yodpijit, Nantakrit; Junsupasen, Suparoek; Sappakittipakorn, Manote; Jongprasithporn, Manutchanok (My University, 2025)
Over the past decade, PM 2.5 pollution has become an increasingly serious environmental concern in Thailand, with one of its primary sources being the open burning of agricultural residues, particularly sugarcane residues. To mitigate this issue, it is essential to develop alternative applications for sugarcane leaves that eliminate the need for burning. This study investigates a sustainable approach by incorporating sugarcane leaves into producing noise insulation mortar boards. The research aims to assess these boards' acoustic performance through a combination of laboratory experiments and field testing. Employing the Design of Experiments (DOE) methodology, mortar samples were prepared with sugarcane leaf content at 2%, 4%, 6%, 8%, and 10% by cement weight to identify the optimal mixture. Analysis of variance (ANOVA) indicated that the sugarcane leaf content had a statistically significant effect on sound pressure level reduction at a 95% confidence level. Both laboratory and field results demonstrated that the 4% sugarcane leaf mixture yielded the highest performance, achieving noise reductions of 20.6 dBA and 23 dBA, respectively. These findings confirm that mortar boards reinforced with sugarcane leaves effectively reduce noise and offer a viable solution for repurposing agricultural residues. This approach contributes to noise pollution mitigation and addresses environmental concerns related to the open burning of biomass.
Keywords: Agricultural residues; ANOVA; noise insulation; sugarcane leaves